An updated strategic research agenda for the integration of radioecology in the european radiation protection research. (October 2021) - Gilbin, Rodolphe; Arnold, Thuro; Beresford, Nicholas A.; Berthomieu, Catherine; Brown, Justin E.; de With, Govert; Horemans, Nele; Madruga, Maria José; Masson, Olivier; Merroun, Mohammed; Michalik, Boguslav; Muikku, Maarit; et al.
Abstract: The ALLIANCE Strategic Research Agenda (SRA) for radioecology is a living document that defines a long-term vision (20 years) of the needs for, and implementation of, research in radioecology in Europe. The initial SRA, published in 2012, included consultation with a wide range of stakeholders (Hinton et al., 2013). This revised version is an update of the research strategy for identified research challenges, and includes a strategy to maintain and develop the associated required capacities for workforce (education and training) and research infrastructures and capabilities. Beyond radioecology, this SRA update constitutes a contribution to the implementation of a Joint Roadmap for radiation protection research in Europe (CONCERT, 2019a). This roadmap, established under the H2020 European Joint Programme CONCERT, provides a common and shared vision for radiation protection research, priority areas and strategic objectives for collaboration within a European radiation protection research programme to 2030 and beyond. Considering the advances made since the first SRA, this updated version presents research challenges and priorities including identified scientific issues that, when successfully resolved, have the potential to impact substantially and strengthen the system and/or practice of the overall radiation protection (game changers) in radioecology with regard to their integration into the global vision of European research in radiation protection. An additional aim of this paper is to encourage contribution from research communities, end users, decision makers and other stakeholders in the evaluation, further advancement and accomplishment of the identified priorities.